Storytelling: An Exchange. - LEWIS, MICHAEL (Paris Review)
An interview between authors Malcolm Gladwell and Michael Lewis is presented. Gladwell's involvement in the magazine "The American Spectator" is addressed. Gladwell notes his background as an undocumented immigrant in the U.S. They discuss Gladwell's book "David and Goliath." They mention moral aspects of Lewis's books. The development of Lewis's book "The Undoing Project" is addressed.